VISUAL SEMANTIC MAPPING BERBASIS KEARIFAN LOKAL SEBAGAI STRATEGI PEMBELAJARAN SENI BUDAYA BAGI SISWA TUNARUNGU - Mochamad Misbahruddin; Mirna Wardatun Nisa’; Taqwi Matus Sholikhah; Mirda Aini Fahma; Dewi Niswatul Fithriyah (STKIP Pesisir Selatan, 2025)
Cultural learning for deaf students requires strategies that emphasize visual, contextual, and meaningful aspects, particularly by utilizing local wisdom of the area where students live, such as the local wisdom of Bojonegoro Regency. One relevant approach is Visual Semantic Mapping (VSM), a visual map-based learning strategy that systematically connects main concepts with subconcepts. This study aims to examine the effectiveness of local wisdom-based Visual Semantic Mapping as a cultural learning strategy for deaf students. The method used is a descriptive qualitative study with a literature study approach and learning observations. The results of the study indicate that the application of local wisdom-based VSM can improve the understanding of cultural concepts, enrich visual vocabulary, and encourage the active involvement of deaf students in learning. This strategy also helps students connect cultural materials with real experiences in their surroundings. Thus, local wisdom-based Visual Semantic Mapping can be used as an alternative inclusive and effective cultural learning strategy for deaf students.